The Political Strategy of The Indonesian Solidarity Party (PSI) In Ende Regency To Win The Most Votes In The 2024 Legislative Elections - Ilham Saputra Sukalumba; Muhammad Ardi Firdiansyah (Internasional Journal of Politics and Public Policy, 2026)
This study aims to analyze the success of the Indonesian Solidarity Party (PSI) in gaining the most votes in the 2024 Legislative Election in Ende Regency. The background of this research is that PSI Ende has succeeded in defeating several major political parties. This research method uses a qualitative approach with a descriptive research type. Data collection was carried out through in-depth interviews, observation, and documentation. Data analysis was carried out qualitatively through the stages of data reduction, data presentation, and conclusion. The results show that the PSI Ende Regency during the 2024 Legislative Election widely used a push political marketing strategy. This is seen in how the PSI Ende Party emphasized that each legislative candidate frequently goes down to the community through door-to-door, community dialogue, distributing party stickers and brochures, and active involvement of legislative candidates to establish communication with voters. To assist its legislative candidates, the PSI Ende Party also built a command center or post in each electoral district. The implementation of the pull political marketing strategy is a supporting strategy to the previous strategy because the PSI Ende Party only uses one mass media for campaigning, namely Facebook. Meanwhile, for the past political marketing strategy, the PSI Ende party does not use it much because the party's position is made as an open and plural party that does not consider ethnicity, race, or religion.